Comparison of the efficacy of gesture‐verbal treatment and doll therapy for managing neuropsychiatric symptoms in older patients with dementia. (23rd August 2018) - Balzotti, Angela; Filograsso, Marianna; Altamura, Claudia; Fairfield, Beth; Bellomo, Antonello; Daddato, Fabio; Vacca, Rosa Anna; Altamura, Mario
Abstract : Background: The prevalence of neuropsychiatric symptoms (NPS) diminishes the quality of life and increases the care burden in patients with dementia. Despite the clinical importance of dementia‐associated NPS, no protocols for treating NPS are already well established. Attention has turned to the effectiveness of nonpharmacological treatments for NPS since their potential safe alternative to pharmacotherapy. Objective: This study is aimed to compare the effects in older individuals with dementia living in a residential care, of two intervention programs, the gesture‐verbal treatment (GVT), a treatment implemented by us on a previous method for word retrieval in individuals with aphasia, and the better‐known doll therapy (DT). The GVT would act on both receptive and expressive language skills, the DT on attachment and emotional connections. Methods: We evaluated NPS by the neuropsychiatric inventory in a total of 30 patients divided into 3 groups, the GVT, the DT, and control groups, using a pre‐post design. The treatment groups completed 12‐week nonpharmacological interventions in addition to standard rehabilitative therapies, while the control group participated only in standard rehabilitative therapies. Results: The DT group showed significant improvements in agitation, irritability, apathy, depression, and delusions relative to controls. The GVT group showed significant improvements in apathy and depression with respect to controls. The DT intervention ameliorated symptoms of agitation compared to the GVT intervention whereas the GVT intervention improved apathy compared to the DT intervention. Conclusion: Improved understanding of the potential therapeutic benefits of different treatments for neuropsychiatric symptoms is crucial for establishing nonpharmacological interventions in dementia.